Biotechnological approaches to plantain and banana improvement at IITA - Vuylsteke, D.R.; Swennen, Rony L. (1992)
Plantains and bananas are an important staple food crop in developing countries. Genetic improvement programmes have been spurred by the rapid spread of black sigatoka disease, but the genus Musa is intractable in terms of conventional breeding strategies. The potential ofbiotechnology in banana and plantain improvement may therefore be considerable. Simple tissue culture techniques, such as shoot-tip culture and embryo culture, can overcome some of the obstacles impeding breeding progress. These techniques have contributed to IlTA's success in the production ofblack sigatoka-resistant plantains. Assistance in the development of tissue culture laboratories has been provided to Nigerian national programmes, thereby strengthening their capability in biotechnology. Cell culture and RFLP mapping, both essential to the future implementation of molecular genetic techniques in Musa improve ment, are being researched in collaboration with advanced laboratories.